2022
DOI: 10.1002/1438-390x.12112
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and growth patterns of Pentaclethra macroloba (Willd.) Kuntze, a hyperdominant tree in the Amazon River estuary

Abstract: Little is known about the life history and environmental factors that regulate the growth rate of hyperdominant trees in flooded Amazonian forests. Pentaclethra macroloba is a hyperdominant tree, and it is widely explored in the Amazon, because its seed oil is a powerful herbal medicine. We evaluated the demographic structure and growth patterns of P. macroloba and tested the effect of the Amazon River flood pulse on its growth. We modeled the growth and determined the age of P. macroloba by analyzing the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 59 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…P. macroloba is native to the Amazon and other South American countries (Guyana, Suriname, French Guiana, Venezuela, Colombia) and Central America and the Caribbean (Honduras, Jamaica, Nicaragua, Panama, Cuba and in Trinidad Tobago) [ 3 , 13 , 39 , 54 ]. It is a pioneer species that has a high density in the Amazon River estuary region [ 5 , 6 , 7 , 55 , 56 ].…”
Section: Taxonomy Occurrence and Botanymentioning
confidence: 99%
See 2 more Smart Citations
“…P. macroloba is native to the Amazon and other South American countries (Guyana, Suriname, French Guiana, Venezuela, Colombia) and Central America and the Caribbean (Honduras, Jamaica, Nicaragua, Panama, Cuba and in Trinidad Tobago) [ 3 , 13 , 39 , 54 ]. It is a pioneer species that has a high density in the Amazon River estuary region [ 5 , 6 , 7 , 55 , 56 ].…”
Section: Taxonomy Occurrence and Botanymentioning
confidence: 99%
“…In regard to Dantas et al [ 6 ], their studies provide foundational knowledge for the formulation of public policies for the sustainable management and conservation of natural resources of P. macroloba and its multiple uses. Thus, the importance of sustainable management of floodplain forests lies in allowing the diversity of their functions, their natural resources and ecosystem services, providing the opportunity for sustainable development of the human population in the Amazon.…”
Section: Taxonomy Occurrence and Botanymentioning
confidence: 99%
See 1 more Smart Citation
“…This species occupies the 10th position in the rank of the hyperdominant plants of the Amazon (ter Steege et al, 2020), it can be found in upland, floodplain and igapó forests (Ferreira et al, 2005;Condé & Tonini, 2013;Carim et al, 2016). P. macroloba is considered a long-lived late secondary species (ecological classification proposed by Budowski (1970)), seedlings can persist for up to 21 years in the shade of the understory and adult trees reaching up to 102 years of age in the floodplain forests of the Amazon estuary (Dantas et al, 2022). This species colonizes secondary forests and gaps very well, even improving soil microbiota and nitrogen fixation (McGee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the ecological and management aspects of the population of P. macroloba in western Amazonia (Dantas et al, 2021a(Dantas et al, , 2021b(Dantas et al, , 2022, making it a worrying situation, as the species is historically exploited by riverside populations and currently by the cosmetics industries. The oil extracted from its seeds has medicinal properties against muscle pain, inflammation, snakebite and even in the treatment of cancer according to reports from the local population of the island of Cotijuba in the State of Pará, Brazil (Crespi & Guerra, 2013).…”
Section: Introductionmentioning
confidence: 99%